The Judicial Pardon Arrangement as a Method of Court Decision in the Reform of Indonesian Criminal Law Procedure - Mufatikhatul Farikhah (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
Judicial Pardon is a new concept formulated in the 2019 Draft of the Criminal Code. The concept refers to the judges’ new powers to forgive defendants who are convicted guilty. However, the formulation of the concept has not been adjusted to the formulation of decision types in the draft of the Criminal Law Procedure. There has to be a harmonization between the Draft of the Criminal Code and the Draft of the Criminal Law Procedure. This article is based on a legal study on the importance of regulating judicial pardon as a form of the court decision. It reveals that judicial pardon is in line with the insignificant principle that if an act already fulfills the elements of a criminal act but is not significant with the essential characteristics of the criminal act, it cannot be declared as a criminal act. However, it is not consistent with the essential nature of a criminal act. In addition, a judicial pardon is a form of shifting punishment towards a flexible balance model from the original one that is absolute. Therefore, it is important to amend the Draft of the Criminal Procedure Law on the types of judges’ decisions. The current judges’ decisions are not compliant with the concept of judicial pardon. The amendment can be processed by adding a decision of conviction without punishment as a type of judge’s decision. The article offers a concept related to legal remedies on judicial pardon as a final and binding decision. Therefore, legal remedies cannot target such decisions.Pengaturan Judicial Pardon Sebagai Bentuk Putusan Pengadilan dalam Pembaharuan Hukum Acara Pidana Indonesia                AbstrakJudicial Pardon merupakan konsep baru yang dirumuskan dalam Rancangan KUHP 2019. Konsep ini merujuk pada kewenangan baru yang diberikan kepada hakim dalam memberikan pemaafan kepada terdakwa yang terbukti bersalah melakukan tindak pidana. Akan tetapi, perumusan konsep tersebut tidak diimbangi dengan perumusan Judicial Pardon sebagai jenis putusan dalam RKUHAP. Dengan demikian, perlu ada harmonisasi antara RUU KUHP dan RKUHAP. Artikel ini ditulis berdasarkan hasil penelitian hukum terkait pentingnya pengaturan Judicial Pardon sebagai bentuk putusan pengadilan. Judicial Pardon sejalan dengan Insignificant Principle. Prinsip ini menyatakan bahwa tidak dapat dinyatakan sebagai suatu pidana terhadap suatu perbuatan yang memenuhi rumusan unsur tindak pidana, akan tetapi tidak sesuai dengan sifat hakiki dari suatu tindak pidana. Selain itu,  Putusan Judicial Pardon merupakan bentuk pergeseran pemidanaan ke arah model keseimbangan yang fleksibel, dari semula bersifat absolut. Sehingga perubahan RKUHAP terkait jenis putusan hakim sangat diperlukan. Jenis-jenis putusan hakim yang saat ini ada dalam KUHAP belum sesuai dengan konsep Judicial Pardon. Perubahan tersebut dapat dilakukan dengan menambahkan putusan salah tanpa pidana sebagai salah satu jenis putusan hakim. Artikel ini menawarkan konsep terkait dengan upaya hukum atas putusan Judicial Pardon dengan menerapkan Judicial Pardon sebagai putusan yang bersifat final and binding. Sehingga terhadap putusan tersebut tidak dapat dilakukan upaya hukum. Kata kunci: judicial pardon, putusan pengadilan, pembaharuan hukum acara pidana.DOI: https://doi.org/10.22304/pjih.v8n1.a1